General Equilibrium in Economies with Infinite Dimensional Commodity Spaces: A Truncation Approach - Gerard van der Laan; Cees Withagen (Tinbergen Institute, 2000)
Mostly infinite dimensional economies can be considered limits offinite dimensional economies, in particular when we think of time orproduct differentiation. We investigate conditions under which sequences of quasi-equilibria in finite dimensional economies converge to a quasi-equilibrium in the infinite dimensional economy. It is shown that convergence indeed occurs if the usual continuity assumption concerning the preference relations for finite dimensional commodity spaces is slightly modified.
Keywords: 330; general equilibrium; truncation; infinite dimensional commodity space; Allgemeines Gleichgewicht; Wohlfahrtstheorie; Theorie